2021
DOI: 10.48550/arxiv.2107.10765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of apsidal motion in eclipsing binaries using TESS data II. A test of internal stellar structure}

A. Claret,
A. Giménez,
D. Baroch
et al.

Abstract: Context. The measurement of apsidal motion rates in eccentric eclipsing binaries is a unique way to gain insight into the internal structure of stars through the internal density concentration parameter, k 2 . High-quality physical parameters of the stellar components, together with precise measurements of the advance of the periastron, are needed for the comparison with values derived from models. Aims. As a product of the Transiting Exoplanet Survey Satellite (TESS) mission, high-precision light curves of a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Baroch et al [271] used TESS data to study apsidal motion in 15 EBs and determine the apsidal periods of nine of these. A comparison of these with theoretical models by Claret et al [272] found good agreement.…”
Section: Standard Ebssupporting
confidence: 59%
“…Baroch et al [271] used TESS data to study apsidal motion in 15 EBs and determine the apsidal periods of nine of these. A comparison of these with theoretical models by Claret et al [272] found good agreement.…”
Section: Standard Ebssupporting
confidence: 59%
“…They depend on the orbital angular frequency (Ω K ), the rotational angular frequencies (ω j ), the moment-ofinertia constants (η j ), and the apsidal-motion constants (k 2j ). We adopted the values of η j and k 2j reported by Claret et al (2021) (see Table 3). The geodesic spin precession rate Ω G,j is much smaller than Ω P,j and was neglected in our calculations.…”
Section: Time Evolution Of the Spin Andmentioning
confidence: 99%
“…This is because the Rossiter-McLaughlin effect is mainly sensitive to the sky-projected obliquity λ, and insensitive to the inclination i of the rotation axis with respect to the line of sight. Because of the need to marginalize over the unknown inclinations of both stars, the theoretical apsidal precession rate was subject to a large uncertainty (Albrecht et al 2009;Claret et al 2010;Claret et al 2021).…”
Section: Introductionmentioning
confidence: 99%